2013
DOI: 10.1115/1.4023986
|View full text |Cite|
|
Sign up to set email alerts
|

Confocal Image-Based Computational Modeling of Nitric Oxide Transport in a Rat Mesenteric Lymphatic Vessel

Abstract: The lymphatic system plays important roles in protein and solute transport as well as in the immune system. Its functionality is vital to proper homeostasis and fluid balance. Lymph may be propelled by intrinsic (active) vessel pumping or passive compression from external tissue movement. With regard to the former, nitric oxide (NO) is known to play an important role modulating lymphatic vessel contraction and vasodilation. Lymphatic endothelial cells (LECs) are sensitive to shear, and increases in flow have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…9B, the electrical stimulation is indeed able to elicit a change in the intrinsic pumping pattern, increasing net forward lymph progression. These observations can be explained based on the following considerations: 1) the shear stress is very low in these vessels and, even during extrinsic contraction, never exceeds 0.25 dyne/cm 2 (Table 1), a value that might be below the threshold for the induction of nitric oxide production (14,32,41); and 2) the source of the electrical stimulus was artificial in our experiments, and it cannot be excluded that the electrical activity of the skeletal muscle could also affect the intrinsic contraction on purely electrical basis, implying a potential electrical interplay between the two pumping mechanisms.…”
Section: Ajp-heart Circ Physiolmentioning
confidence: 99%
“…9B, the electrical stimulation is indeed able to elicit a change in the intrinsic pumping pattern, increasing net forward lymph progression. These observations can be explained based on the following considerations: 1) the shear stress is very low in these vessels and, even during extrinsic contraction, never exceeds 0.25 dyne/cm 2 (Table 1), a value that might be below the threshold for the induction of nitric oxide production (14,32,41); and 2) the source of the electrical stimulus was artificial in our experiments, and it cannot be excluded that the electrical activity of the skeletal muscle could also affect the intrinsic contraction on purely electrical basis, implying a potential electrical interplay between the two pumping mechanisms.…”
Section: Ajp-heart Circ Physiolmentioning
confidence: 99%
“…Increasing shear stress stimulates the production of NO by LECs (Bohlen et al, 2011; Bohlen et al, 2009) causing hyperpolarization of LMCs, which inhibits the pacemaker activity due to increased cGMP levels (von der Weid, 1998; von der Weid et al, 2001). Interestingly, computational modeling of NO transport in the valvular area of the lymphangion has demonstrated that the high NO concentration observed there is attributed to flow stagnation in these locations (Figure 3, left) (Wilson et al, 2013). Due to the highly viscous nature of the flow, fluid filling the space behind the valve leaflets is essentially stagnant (although it does move in slowly rotating vortex-like structures).…”
Section: Lymph Propulsion Between Lymphangionsmentioning
confidence: 99%
“…Note that Wilson et al prescribed that NO production increases with flow-induced shear stress, so the LECs in the stagnant zone are actually producing less NO than those exposed to the mainstream of the flow, especially on the inner surface of the valve leaflets (Figure 3, right). Thus, the flow phenomena end up being the major determinants of NO concentration distribution and could possibly affect other signaling pathways (Wilson et al, 2013). As this study was done with a stationary geometry, it remains to be determined how the motion of the leaflets towards the wall or back to the center of the lumen might influence these predicted NO distribution patterns.…”
Section: Lymph Propulsion Between Lymphangionsmentioning
confidence: 99%
See 2 more Smart Citations